CORRECTIONAL AND EDUCATIONAL TECHNOLOGY OF SOCIALIZATION OF PUPILS AT SPECIAL SECONDARY SCHOOL - Tatianchykova, Iryna; Tatianchykov, Andrii; Knyazheva, Irina; Boiko, Svitlana (Revista Inclusiones, 2020)
The article reveals the problem of children’s socialization with intellectual disabilities; directions of psychological and pedagogical support of their socialization at the stage of individualization in the conditions of special secondary school. This problem is very relevant, there is a change in human behaviour, that provokes the corresponding social tension in society because of the modern conditions of reforming the country, violation of traditional mechanisms of social regulation and interaction and due to the formation of market relations. It should be noted that negative influences in society, first of all, affect the most vulnerable part of it, these are children, and especially the socalled "risk groups", which include children with disabilities. As a result, the problem of children's disabilities and mental illness is exacerbated. Experience has shown that children often face certain serious problems that they are unable to solve on their own. They need careful attention and especially help from the state and qualified specialists: social educators and psychologists. That is why the processes of aggravation of social relations and socialization, in general, require rethinking, analysis and generalization. There is an urgent need to develop a social policy strategy at both the state and the regional levels. Educational, training and rehabilitation institutions, there is a targeted impact on children with disabilities there, should play an important role in managing the process of social development of their pupils and achieving their general level of social persuasion.